Easily attainable and low immunogenic stem cells from exfoliated deciduous teeth enhanced the in vivo bone regeneration ability of gelatin/bioactive glass microsphere composite scaffolds - Xiong, Huacui; Zhao, Fujian; Peng, Yuqi; Li, Meimei; Qiu, Huanhuan; Chen, Ke (Frontiers in Bioengineering and Biotechnology, 2022)
Repair of critical-size bone defects remains a considerable challenge in the clinic. The most critical cause for incomplete healing is that osteoprogenitors cannot migrate to the central portion of the defects. Herein, stem cells from exfoliated deciduous teeth (SHED) with the properties of easy attainability and low immunogenicity were loaded into gelatin/bioactive glass (GEL/BGM) scaffolds to construct GEL/BGM+SHED engineering scaffolds. An in vitro study showed that BGM could augment the osteogenic differentiation of SHED by activating the AMPK signaling cascade, as confirmed by the elevated expression of osteogenic-related genes, and enhanced ALP activity and mineralization formation in SHED. After implantation in the critical bone defect model, GEL/BGM+SHED scaffolds exhibited low immunogenicity and significantly enhanced new bone formation in the center of the defect. These results indicated that GEL/BGM+SHED scaffolds present a new promising strategy for critical-size bone healing.